Influence of soluble salt matrix on mechanochemical synthesis of lanthanum cobaltate nanoparticles - Sompech S. (2014)
Mechanochemical reaction of lanthanum cobaltate (LaCoO 3) nanoparticles was performed by milling mixtures of LaCl 3-7H 2O, CoCl 2 and Na 2CO 3, with no addition and addition of soluble salt matrix (NaCl). The purposes of this work were to synthesize LaCoO 3 nanoparticles via mechanochemical process and to study the effect of soluble salt matrix on the average particle size and specific surface area. The three-stage process consisting of mechanical milling, subsequent heating and washing with distilled water was used to synthesize of LaCoO 3 nanoparticles. The results indicated that the average particle size (D[4,3]) and the specific surface area are as a function of the soluble salt matrix concentration. Moreover, SEM images revealed that the addition of soluble salt matrix can improve the dispersion of LaCoO 3, nanoparticles.